THE EFFECTS OF THE COVID-19 PANDEMIC ON THE EDUCATION OF HIGH SCHOOL STUDENTS - Monica TURTUREAN (Association of Social and Educational Innovation, 2021)
The COVID-19 pandemic and the measures taken to limit its spread have negatively impacted the entire world, humanity has been subjected to severe pressure and failed to manage it, which has led to major problems on all levels: educational, relational, economic, but also physical and emotional health problems that will hardly lead to a solution. The most affected by this pandemic were the students from pre-university education who, for a long time, were deprived of a good quality education, because, on the one hand, the teachers were not prepared to teach online, they did not have the necessary software, they didn't know how to teach online, on the other hand, students did not have the electronic devices or the necessary technology to participate in online activities and, in the absence of a digital infrastructure, there could be no unitary regulations related to teaching and interaction with students. A big problem was that teachers did not have digital skills; according to Horga, Irina (coord.). 2020, only 4% of the total training courses organized by the Houses of the Teaching Staff in the period 2013-2018 aimed to develop digital skills / the use of ICT in the teaching-learning-evaluation process. Really affected by this pandemic were students from rural areas who, due to the precarious economic situation of their parents, could not afford to buy electronic tools to connect online to class. One year after the first day when schools in Romania closed and education was transferred online, almost one million children enrolled in pre-university education in rural areas are still in critical situations. mentioned World Vision Romania, which underlined those important measures must be taken to overcome these accumulated learning losses during the time when the classes took place online. 40% of students from disadvantaged backgrounds, most of them enrolled in rural schools, did not go to school online, for various reasons. (https://worldvision.ro/implica-te/persoane-fizice/fondul-de-urgenta/). In this context, we conducted a comparative study to find out to what extent students in rural areas were disadvantaged by this pandemic, compared to students in urban areas.